2019
DOI: 10.1093/bjc/azz040
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Radical Economic Restructuring in Truancy from School and Engagement in Crime

Abstract: Of late, criminologists have become acutely aware of the relationship between school outcomes and engagement in crime as an adult. This phenomenon—which has come to be known as the ‘school-to-prison-pipeline’—has been studied in North America and the United Kingdom, and requires longitudinal data sets. Typically, these studies approach the phenomenon from an individualist perspective and examine truancy in terms of the truants’ attitudes, academic achievement or their home life. What remains unclear, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…We focus on the UK's former coalmining communities as a case study in sudden industrial decline, which came about as the government closed down the publiclyowned mining industry in the mid-1980s. Since many former mining communities had been built specifically to house workers employed in the mines, and given the substantial shares of employment of the local population in the mines even in the early 1980s, the closure implied a very significant economic shock to these communities (Farrall, et al, 2020). While we are not able to identify a regression model that specifically captures the impact of a coal-mining heritage on political views and engagement (as there is no exogenous variation), we use a matching approach to compare the values and social norms of individuals in coal-mining areas, to very similar individuals in areas that are otherwise very similar, but lack the common narrative of sudden industrial decline.…”
Section: Methodsmentioning
confidence: 99%
“…We focus on the UK's former coalmining communities as a case study in sudden industrial decline, which came about as the government closed down the publiclyowned mining industry in the mid-1980s. Since many former mining communities had been built specifically to house workers employed in the mines, and given the substantial shares of employment of the local population in the mines even in the early 1980s, the closure implied a very significant economic shock to these communities (Farrall, et al, 2020). While we are not able to identify a regression model that specifically captures the impact of a coal-mining heritage on political views and engagement (as there is no exogenous variation), we use a matching approach to compare the values and social norms of individuals in coal-mining areas, to very similar individuals in areas that are otherwise very similar, but lack the common narrative of sudden industrial decline.…”
Section: Methodsmentioning
confidence: 99%
“…Truancy is often found to be a predictor of violence in adolescence and adulthood (Cardwell et al, 2019; Farrall et al, 2020; Farrington, 1991; 1998; Garry, 1996; Hansen, 2003; Hawkins et al, 2000; Hawkins et al 1998; Katsiyannis et al, 2013; Loeber & Farrington, 1998; Rocque et al, 2017; Sutphen et al, 2010; White et al, 2001; Zhang et al, 2007, 2010). Being absent from school can place young people in situations that may create opportunities for violence (Henry et al, 1999; Henry & Huizinga, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bully victimization and truancy are related to violent behavior not only in adolescence but longitudinally into adulthood as well (Farrall et al, 2020; Farrington, 1991, 1998; Garry, 1996; Ttofi et al, 2012). Yet most research separately examines how truancy and bully victimization are independently related to violent behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Time series analyses have shown that reduced welfare spending at a time of crisis was associated with higher rates of property crime (Jennings et al 2012. More recent work using cohort studies suggests that children growing up 3 in areas that experienced economic restructuring were more likely to have truanted from school and been in contact with the criminal justice system in later life (Farrall et al 2019a(Farrall et al , 2019b . Most interestingly, Thatcherism seems to have increased a whole generation's fear of crime via a political socialisation effect (Farrall 2006, Gray et al 2019.…”
Section: The Political Economy Of Crimementioning
confidence: 99%